Mating and egg-laying behaviour of the Southeast Asian apple snail Pila pesmei (Morlet, 1889) (Caenogastropoda, Ampullariidae) - Supunya Annate; Ng, Ting Hui; Chirasak Sutcharit; Somsak Panha (Pensoft Publishers, 2025)
The apple snail Pila pesmei is an economically valuable freshwater snail in mainland Southeast Asia whose populations have recently dramatically declined. Although conservation concerns have been rising in the region, the lack of basic knowledge of its reproductive biology remains an obstacle to its conservation. This study describes the mating and egg-laying behaviours of P. pesmei under laboratory conditions using continuous video recordings. Fifteen mating behaviours were recorded in four mating phases: pre-courtship, courtship, copulation, and post-copulation. Mating sequences were variable, especially in the courtship phase. However, many males performed a common courtship sequence of mate probing, mounting, shell circling, and positioning. When a female performed a variety of actions against the male’s approach, males then performed various alternative courtship sequences. The egg-laying process was similar among different females. They burrowed into the soil substrate to lay eggs. A total of six behaviours were recorded in the egg-laying process: crawling, resting, withdrawal, burrowing, egg depositing, and aestivating. Females did not return to the water after laying eggs but remained in the egg-laying cavity with their egg masses. This behaviour has not been reported in any other Pila species to date. Overall, our examination revealed the previously unknown mating and egg-laying processes in P. pesmei, which included some distinct behaviours and increased the basic knowledge of its reproductive biology.